Planeamiento estratégico para mejorar la gestión organizacional de la empresa de Sistemas y Seguridad del Perú SAC - Vásquez Linares, Luis (2012)
This work aims to develop a strategic plan to improve the management in the company: "security systems the Peru SAC (SYS PERU)", whose line of business is the installation of electronic security systems anti intrusion. It has a quantitative approach and descriptive kind, the population comprises the market of electrical safety anti intrusion of the City of Trujillo in which it operates SYS PERU in 2011, the sample is made up of six companies and eight workers, it has used material bibliographic, surveys, direct observation and interviews to gather information. To realize the proposed objective of the analysis was carried out an external and internal studio, getting to determine that the environment offers a number of opportunities that can be exploited, the company has important strengths that can capitalize on these opportunities and to minimize environmental threats but also has significant weaknesses that prevent it from being competitive. It also defined the vision, mission, policies, Long Term Goals, Strategies and Actions to follow that will help the company become more competitive, improve their management and become a part of the market. The market for electrical safety anti intrusion has had significant growth in recent years due to the growth of the construction sector and paradoxically a increasing insecurity, an effort by the company to commit human and financial resources that will achieve the objectives, conclusions and proposed recommendations.